Strategi Komunikasi Pemasaran Terpadu Dinas Pariwisata dan Kebudayaan Kabupaten Bangli dalam Memperkenalkan Batur Geopark Sebagai Ikon Pariwisata Kintamani - Cahya Wulantari, Dewa Ayu Anggun; Pascarani, Ni Nyoman Dewi; Pradipta, Ade Devia (E-Jurnal Medium, 2018)
ABSTRACT The title of this study is The Strategy of Integrated Marketing Communication by Tourism and Culture Departement of Bangli Regency in Introducing Batur Geopark as Kintamani Landmark. In 2008 Batur was promoted to become one of member in Global Geopark Network. Finally in 2012 after four years, Batur become the first Global Geopark Network in Indonesia that was approved by UNESCO. Tourism and Culture Departement of Bangli Regency are responsible in marketing and introducing Batur Geopark. This study aimed to find out the strategy of integrated marketing communication by Tourism and Culture Departement of Bangli Regency in introducing Batur Geopark to wide community. This study is a descriptive qualitative research. The data was taken through interview, observation and documentation. Informant determination technique in this research was done by purposive sampling. In this study can be concluded that the strategy of integrated marketing communication by Tourism and Culture Departement of Bangli Regency were used two elements promotional mix of five elements promotional mix. The two elements promotional mix that used are: 1). Advertising, such as using billboard, booklet, website, Facebook, and Instagram. 2). Public Relation, such as by socialization to the society, held seminars about Batur Geopark, training for tracking guides and held Batur lake festival. Whereas the three elements promotional mix such as, Sales Promotion, Personal Selling, and Dirrect Selling were not used maximally by Tourism and Culture Departement of Bangli Regency . Keywords: Marketing Communication, Batur, Geopark, Tourism.